Beta-silicon nitride coated spherical aluminum nitride and preparation method thereof

The dense β-silicon nitride layer was generated on the surface of spherical aluminum nitride by direct nitriding of silicon powder, which solved the silicon carbide problem caused by the carbon thermal reduction method, and achieved high thermal conductivity and good insulation of silicon nitride coated spherical nitrogen Aluminum composite material.

CN119409510AActive Publication Date: 2025-02-11JIANGSU NOVORAY NEW MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411568349.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The prior art uses the carbon-thermal reduction method to prepare silicon nitride layers, which easily produces silicon carbide and affects the insulation performance of the product.

Method used

The direct nitriding method of silicon powder is used to generate a dense β-silicon nitride layer on the surface of spherical aluminum nitride, avoiding the formation of silicon carbide. The method includes spray granulation, low-temperature glue discharge and high-temperature sintering to ensure the density and high thermal conductivity of the silicon nitride layer.

Benefits of technology

Silicon carbide-free silicon nitride coated spherical aluminum nitride composite material is realized, which improves the thermal conductivity and insulation performance of the product, and avoids the problems of hydration and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409510A_ABST
    Figure CN119409510A_ABST
Patent Text Reader

Abstract

The invention discloses beta-silicon nitride coated spherical aluminum nitride and a preparation method thereof, and belongs to the field of preparation of silicon nitride-spherical aluminum nitride composites.The preparation method is characterized in that a compact beta-silicon nitride layer is coated, nitrided and sintered on the surface of spherical aluminum nitride, and composite particles with the surfaces coated with the compact beta-silicon nitride layer are obtained; the problems that silicon carbide is introduced while aluminum nitride is hydrated, and the insulating property of a product is reduced are solved, and the method is mainly applied to production of the silicon nitride-spherical aluminum nitride composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of silicon nitride modified spherical aluminum nitride, and in particular to beta-silicon nitride coated spherical aluminum nitride and a preparation method thereof. Background Art

[0002] A new silicon nitride-coated spherical aluminum nitride product is prepared by coating the surface of spherical aluminum nitride with a dense, highly thermally conductive β-silicon nitride layer. This preparation method utilizes the thermal conductivity of β-silicon nitride to form a solid and dense, highly thermally conductive protective layer on the outer surface of spherical aluminum nitride. This not only significantly improves the waterproof performance of the product, but also lays a solid foundation for its performance in various complex application scenarios. The structure of this product gives it outstanding advantages in thermal conductivity, insulation, etc., and is expected to play an important role in multiple fields such as electronics and materials.

[0003] Application number: JP2023088509A, named as a method for manufacturing silicon oxide coated aluminum nitride powder and silicon oxide coated aluminum nitride powder, the aluminum nitride powder is stirred and sprayed with a silane coupling agent for dry mixing, and then the aluminum nitride powder coated with the silane coupling agent is heated to 500-800°C in air to form a silicon oxide coating layer on the surface of the aluminum nitride powder to obtain silicon oxide coated aluminum nitride powder, and a silicon oxide layer is covered on the surface of the aluminum nitride to achieve a waterproofing effect.

[0004] The above patent has the following defects: the surface of aluminum nitride is coated with a silicon dioxide layer with low thermal conductivity, which will cause the overall thermal conductivity of aluminum nitride to decrease.

[0005] Application number: JP7229328B1, titled as a method for manufacturing silicon nitride coated aluminum nitride powder, wherein a layer of organic silicon layer is coated on the surface of aluminum nitride powder with a silane coupling agent of a specific structure, and then the organic silicon coated aluminum nitride powder is heated to 1300-1600°C in a nitrogen atmosphere for reduction nitridation, and a silicon nitride film is formed on the surface of the aluminum nitride powder to obtain silicon nitride coated aluminum nitride powder, and a thin silicon nitride layer is coated on the surface of the aluminum nitride powder to achieve the effects of waterproofing and high thermal conductivity.

[0006] The above patent has the following defects: the use of carbon thermal reduction method to prepare the silicon nitride layer will inevitably produce some silicon carbide, which will affect the insulation performance of the product.

[0007] To this end, our company proposed a study on β-silicon nitride-coated spherical aluminum nitride and its preparation method. Summary of the invention

[0008] Purpose of the invention: The present invention solves the problem that in the prior art, a silicon nitride layer is prepared by a carbon thermal reduction method, which inevitably produces some silicon carbide and affects the insulation performance of the product.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] A spherical aluminum nitride coated with β-silicon nitride, characterized in that a layer of dense β-silicon nitride layer is coated, nitrided, and sintered on the surface of the spherical aluminum nitride to obtain composite particles coated with a dense β-silicon nitride layer on the surface:

[0011] 3Si+2N2=Si3N4.

[0012] A method for preparing β-silicon nitride coated spherical aluminum nitride, characterized in that:

[0013] Step 1: Slurry preparation

[0014] Submicron or micron-sized high-purity silicon powder, β-silicon nitride, spherical aluminum nitride particles, sintering aids and binder raw materials are mixed, and then an organic solvent is added and stirred to obtain a spray granulation slurry;

[0015] Step 2: Spherical aluminum nitride surface coated with reaction layer

[0016] The spray granulation slurry prepared in step 1 is placed in a spray dryer and spray-dried into granulated powder, so that the surface of the spherical aluminum nitride is coated with a reaction layer of a mixture of silicon, β-silicon nitride and a sintering aid;

[0017] Step 3: Low temperature debinding

[0018] The powder obtained in step 2 is placed in a sagger and placed in a sintering furnace for low-temperature debinding to completely decompose the organic matter;

[0019] Step 4: In-situ synthesis of silicon nitride coating after debinding

[0020] The powder after complete binder removal in step 3 is vacuumized in situ, calcined at normal pressure and high temperature in a nitrogen atmosphere, and kept warm for 1h-5h to synthesize a β-silicon nitride layer by direct nitridation of silicon powder and densify it to obtain a spherical aluminum nitride product with a surface coated with dense β-silicon nitride.

[0021] Preferably, the median particle size D50 of the high-purity silicon powder is between 0.1 μm and 2 μm, the median particle size D50 of β-silicon nitride is between 0.1 μm and 5 μm, β-silicon nitride accounts for 0.2-2.5% of the mass of spherical aluminum nitride, high-purity silicon powder accounts for 2.0-5.0%, and sintering aids account for 0.01-0.20%.

[0022] Preferably, the outlet air temperature of the spray drying is 80-100°C, the debinding process is carried out in an air atmosphere of 300-600°C, and the calcination temperature is 1450-1750°C.

[0023] Preferably, the β-silicon nitride-coated spherical aluminum nitride prepared according to the preparation method of β-silicon nitride-coated spherical aluminum nitride is used alone or in combination with silicon nitride in thermal conductive applications of organic silicon systems.

[0024] The present invention has the following beneficial effects:

[0025] (1) A silicon nitride layer is formed on the surface of spherical aluminum nitride by using a silicon powder direct nitridation process. Compared with the carbon thermal reduction process, the possibility of silicon carbide formation is avoided.

[0026] (2) Compared with the millimeter-scale granulation process such as centrifugal granulation, the spray granulation process uses spherical aluminum nitride as the core and uniformly coats the core with a layer of micron-scale silicon powder & β-silicon nitride.

[0027] (3) Submicron or micron-grade silicon powder (D50 = 0.1-2 μm) and β-silicon nitride (D50 = 0.1-5 μm) are selected. After processing, the surface of the particles is densely coated and the coating layer thickness is relatively thin. While the coating is dense, the hydration of the spherical aluminum nitride is avoided and the influence on the thermal conductivity of the spherical aluminum nitride is reduced.

[0028] (4) The spherical aluminum nitride particles coating the reaction layer are debinded at a low temperature of 300-600°C, and then sintered in situ at a high temperature after debinding to avoid the problem of the coating layer falling off due to movement after debinding. At the same time, the low-temperature debinding can fully debind while avoiding damage to the furnace body and sagger.

[0029] (5) Using a mixture of silicon powder and β-silicon nitride as a reaction layer to generate silicon nitride can increase the reaction temperature to above 1410°C, the melting point of silicon. At a high temperature of 1450-1750°C, silicon nitride is rapidly generated and fully converted into sintered, dense, and highly thermally conductive β-silicon nitride, thereby avoiding insufficient nitridation caused by silicon melting.

[0030] (6) A spherical aluminum nitride composite material coated with a dense silicon nitride layer, wherein the thickness of the silicon nitride layer is 0.1-10 μm, the α-silicon nitride content is less than 3%, the silicon residue is less than 3%, and no silicon carbide is contained.

[0031] Test method for β-silicon nitride coated spherical aluminum nitride

[0032] (1) Silicon nitride layer thickness:

[0033] The spherical aluminum nitride powder with a dense β-silicon nitride layer on the surface is cured by epoxy resin and then polished to expose the cut spherical aluminum nitride particles. The maximum and minimum values ​​of the β-silicon nitride layer thickness are measured by scanning electron microscopy.

[0034] (2) α-silicon nitride, silicon, and β-silicon nitride content;

[0035] The spherical aluminum nitride powder with a dense β-silicon nitride layer on the surface was measured using XRD to calculate the proportion of various phases.

[0036] (3) Silicon carbide content;

[0037] The spherical aluminum nitride powder with a dense β-silicon nitride layer on the surface is digested, and the β-silicon nitride layer, spherical aluminum nitride, and sintering aid are digested in sequence. After digestion, the mass of the indigestible matter is weighed to obtain the silicon carbide content.

[0038] (4) Thermal conductivity

[0039] The composite material is prepared into a silicone gasket, and the thermal conductivity of the silicone gasket is measured under the D5470 standard.

[0040] (5)PH

[0041] The composite material was prepared into an aqueous solution, and the pH value of the aqueous solution was measured using a pH meter after magnetic stirring for 30 minutes. The waterproofing performance of aluminum nitride was tested by taking advantage of the fact that aluminum nitride would produce ammonia gas after contacting with water, and ammonia gas would dissolve in water to increase the pH value of the aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the XRD pattern of the composite material obtained in Example 4. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0044] A β-silicon nitride coated spherical aluminum nitride, characterized in that a dense β-silicon nitride layer is synthesized and sintered on the surface of the spherical aluminum nitride, using a silicon powder direct nitridation method:

[0045] 3Si+2N2=Si3N4

[0046] The composite particles which do not contain silicon carbide and whose surfaces are covered with a dense β-silicon nitride layer are obtained.

[0047] A method for preparing spherical aluminum nitride coated with β-silicon nitride, characterized in that:

[0048] Step 1: Granulation slurry preparation:

[0049] The coating materials are submicron or micron-grade high-purity silicon powder and β-silicon nitride. The median particle size D50 of the high-purity silicon powder is between 0.1μm and 2μm, and the median particle size D50 of the β-silicon nitride is between 0.1μm and 5μm.

[0050] Then, the spherical aluminum nitride particles as the core, 0.2-2.5% of beta-silicon nitride by mass of the spherical aluminum nitride, 2.0-5.0% of high-purity silicon powder, 0.01-0.20% of sintering aid and a binder are stirred and mixed in an organic solvent solution to obtain a spray granulation slurry.

[0051] Step 2: Spherical aluminum nitride surface coated with reaction layer:

[0052] Using the spray granulation process, the spray granulation slurry in step 1 is spray-dried into granulated powder under the condition of controlling the outlet air temperature at 80-100° C., so that the surface of the spherical aluminum nitride is coated with a reaction layer of a mixture of silicon, β-silicon nitride and a sintering aid.

[0053] Step 3: Low temperature debinding:

[0054] The powder obtained in step 2 is placed in a sagger, placed in a sintering furnace, and debinded at 300-600°C in an air atmosphere to completely decompose the organic matter.

[0055] Step 4: In-situ synthesis of coated silicon nitride after debinding:

[0056] After the debinding is completed in step 3, the powder is evacuated in situ, heated to 1450-1750°C at normal pressure in a nitrogen atmosphere, and calcined for 1h-5h to synthesize a β-silicon nitride layer by direct nitridation of silicon powder and densify it to obtain a spherical aluminum nitride product with a surface coated with dense β-silicon nitride.

[0057] Example 1

[0058] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.1μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated, the granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h, then vacuumed, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0059] The detection performance of the product of Example 1 is as follows:

[0060] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.6μm <3% <3% 5.4W 7.2

[0061] Example 2

[0062] 200g silicon powder with D50=2.0μm, 70g β-silicon nitride with D50=5.0μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0063] The detection performance of the product of Example 2 is as follows:

[0064] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 6.8-10.0μm <3% <3% 4.7W 7.6

[0065] Example 3

[0066] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 300℃ in a vacuum sintering furnace for 6h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0067] The detection performance of the product in Example 3 is as follows:

[0068]

[0069]

[0070] Example 4

[0071] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated, the granulated powder is put into a sagger, and the binder is debonded at 600℃ in a vacuum sintering furnace for 3h, then vacuumed, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0072] The detection performance of the product of Example 4 is as follows:

[0073] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-2.6μm <3% <3% 5.2W 7.1

[0074] Example 5

[0075] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated, the granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h, then vacuumed, nitrogen is introduced, the temperature is raised to 1450℃, and the temperature is kept and calcined for 5h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0076] The detection performance of the product of Example 5 is as follows:

[0077] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-3.1μm <3% <3% 5.1W 7.2

[0078] Example 6

[0079] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1750℃, and the temperature is kept for calcination for 1h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0080] The detection performance of the product of Example 6 is as follows:

[0081] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-3.6μm <3% <3% 5.0W 7.0

[0082] Example 7

[0083] 100g silicon powder with D50=0.1μm, 10g β-silicon nitride with D50=0.3μm, 0.5g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept and calcined for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0084] The detection performance of the product of Example 7 is as follows:

[0085] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-4.2μm <3% <3% 5.3W 8.4

[0086] Example 8

[0087] 100g silicon powder with D50=0.1μm, 125g β-silicon nitride with D50=0.3μm, 0.5g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept and calcined for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0088] The detection performance of the product of Example 8 is as follows:

[0089] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.5μm <3% <3% 5.8W 7.3

[0090] Example 9

[0091] 100g silicon powder with D50=0.1μm, 125g β-silicon nitride with D50=0.3μm, 10g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0092] The detection performance of the product of Example 9 is as follows:

[0093] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.3μm <3% <3% 6.1W 6.9

[0094] Example 10

[0095] 100g silicon powder with D50=0.1μm, 10g β-silicon nitride with D50=0.3μm, 10g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0096] The detection performance of the product of Example 10 is as follows:

[0097] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-3.9μm <3% <3% 5.4W 8.3

[0098] Embodiment 11

[0099] 250g silicon powder with D50=0.1μm, 10g β-silicon nitride with D50=0.3μm, 0.5g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0100] The detection performance of the product of Example 11 is as follows:

[0101]

[0102]

[0103] Example 12

[0104] 250g silicon powder with D50=0.1μm, 125g β-silicon nitride with D50=0.3μm, 0.5g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept and calcined for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0105] The detection performance of the product of Example 12 is as follows:

[0106] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.4μm <3% <3% 5.8W 7.2

[0107] Embodiment 13

[0108] 250g silicon powder with D50=0.1μm, 125g β-silicon nitride with D50=0.3μm, 10g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0109] The detection performance of the product of Example 13 is as follows:

[0110] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.2μm <3% <3% 6.0W 7.0

[0111] Embodiment 14

[0112] 250g silicon powder with D50=0.1μm, 10g β-silicon nitride with D50=0.3μm, 10g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0113] The detection performance of the product of Example 14 is as follows:

[0114] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-9.2μm <3% <3% 5.6W 8.3

[0115] Comparative Example 1

[0116] 200g silicon powder with D50=4.0μm, 70g β-silicon nitride with D50=7.0μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept and calcined for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0117] The detection performance of the product of Comparative Example 1 is as follows:

[0118] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 4.3-13μm <3% 7.4% 3.1W 8.4

[0119] Compared with Example 2: Silicon powder with too coarse particle size will cause the silicon nitride layer to be too thick and not dense, which will greatly reduce the thermal conductivity and the degree of water resistance. At the same time, silicon powder with too coarse particle size is not easy to be completely nitrided, and residual silicon will be generated.

[0120] Comparative Example 2

[0121] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 150°C in a vacuum sintering furnace for 6h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1600°C, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer coated on the surface.

[0122] The detection performance of the product of Comparative Example 2 is as follows:

[0123]

[0124]

[0125] Compared with Example 3: at 150°C low-temperature debinding, the binder is not completely decomposed, and the residual carbon causes the silicon powder to generate silicon carbide, which reduces the insulation performance of the product.

[0126] Comparative Example 3

[0127] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.1μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated, the granulated powder is put into a sagger, debinded at 450℃ in a muffle furnace for 4h, and then the debinded powder is moved to a vacuum sintering furnace, evacuated, nitrogen is introduced, the temperature is raised to 1600℃, and the temperature is kept for calcination for 3h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0128] The detection performance of the product of Comparative Example 3 is as follows:

[0129] Silicon nitride layer thickness α-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-2.4μm <3% <3% 5.6W 8.2

[0130] Compared with Example 1: After debinding in the muffle furnace, the non-in-situ debinding is moved to the vacuum sintering furnace, which will result in the spherical aluminum nitride surface being unable to be bonded by the binder, and only the silicon powder and β-silicon nitride powder piled together are displaced, resulting in uneven thickness of the reaction layer on the particle surface. After sintering, part of the spherical aluminum nitride surface is not covered by the silicon nitride layer, resulting in a decrease in waterproof performance and an increase in pH value.

[0131] Comparative Example 4

[0132] 200g silicon powder with D50=0.1μm, 70g β-silicon nitride with D50=0.3μm, 6g sintering aid with D50=50nm, 5000g spherical aluminum nitride and 100g binder are stirred and mixed in an organic solvent, then spray granulated. The granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 6h. Then, vacuum is evacuated, nitrogen is introduced, the temperature is raised to 1800℃, and the temperature is kept for calcination for 1h to obtain a spherical aluminum nitride composite material with a dense silicon nitride layer on the surface.

[0133] The detection performance of the product of Comparative Example 4 is as follows:

[0134]

[0135]

[0136] Compared with Example 6: When the sintering temperature is too high, silicon nitride decomposes, the silicon nitride coating layer is not dense, and the waterproof performance is reduced.

[0137] Comparative Example 5

[0138] 270g of silicon powder with D50=0.1μm, 6g of sintering aid with D50=50nm, 5000g of spherical aluminum nitride, and 100g of binder are stirred and mixed in an organic solvent, and the granulated powder is put into a sagger, and the binder is debonded at 450℃ in a vacuum sintering furnace for 4h, then vacuumed, nitrogen is introduced, the temperature is raised to 1300℃, and the temperature is kept and calcined for 3h to obtain a spherical aluminum nitride composite material with an α-silicon nitride layer on the surface.

[0139] The detection performance of the product of Comparative Example 5 is as follows:

[0140] Silicon nitride layer thickness β-Silicon Nitride Content Silicon content Thermal conductivity PH 0.1-1.7μm <3% <3% 4.6W 8.4

[0141] Compared with Example 1: When the sintering temperature is lowered, the silicon powder will not melt during nitridation, but the lower sintering temperature will not convert α-silicon nitride into high thermal conductivity β-silicon nitride, and the sintering is not dense, and the thermal conductivity of the final composite particles is lower than that of the composite particles coated with β-silicon nitride.

[0142] Comparative Example 6

[0143] The data of the spherical aluminum nitride used in the above examples and comparative examples are as follows:

[0144] Silicon nitride layer thickness β-Silicon Nitride Content Silicon content Thermal conductivity PH 0μm <3% <3% 6.6W 9.1

[0145] Compared with the composite material coated with silicon nitride layer, the uncoated spherical aluminum nitride is easy to hydrate.

[0146] The following is a comparison table of the examples and comparative examples:

[0147] Examples 1-14

[0148]

[0149]

[0150] Comparative Examples 1-6

[0151]

[0152] In summary, the coated spherical aluminum nitride obtained in Examples 1-14 of the present invention has a smaller coating thickness and a higher thermal conductivity. The more uniform the coating, the denser the coating layer, the better the waterproof performance, and the closer the pH value is to neutral. From the data of Examples 1-14, Examples 8, 9, 12, and 13 have outstanding effects.

[0153] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A spherical aluminum nitride coated with β-silicon nitride, characterized in that: A dense beta-silicon nitride layer is coated, nitrided and sintered on the surface of spherical aluminum nitride to obtain composite particles with a dense beta-silicon nitride layer coated on the surface.

2. A method for preparing β-silicon nitride coated spherical aluminum nitride, characterized in that: Step 1: slurry preparation; Submicron or micron-sized high-purity silicon powder, β-silicon nitride, spherical aluminum nitride particles, sintering aids and binder raw materials are mixed, and then an organic solvent is added and stirred to obtain a spray granulation slurry; Step 2: coating the surface of spherical aluminum nitride with a reaction layer; The spray granulation slurry prepared in step 1 is placed in a spray dryer and spray-dried into granulated powder, so that the surface of the spherical aluminum nitride is coated with a reaction layer of a mixture of silicon, β-silicon nitride and a sintering aid; Step 3: Low temperature debinding; The powder obtained in step 2 is placed in a sagger and placed in a sintering furnace for low-temperature debinding to completely decompose the organic matter; Step 4: In-situ synthesis of coated silicon nitride after debinding; The powder after complete binder removal in step 3 is vacuumized in situ, calcined at normal pressure and high temperature in a nitrogen atmosphere, and kept warm for 1h-5h to synthesize a β-silicon nitride layer by direct nitridation of silicon powder and densify it to obtain a spherical aluminum nitride product with a surface coated with dense β-silicon nitride.

3. The method for preparing β-silicon nitride-coated spherical aluminum nitride according to claim 2, characterized in that: The median particle size D50 of the high-purity silicon powder is between 0.1μm and 2μm, and the median particle size D50 of the beta-silicon nitride is between 0.1μm and 5μm; the mass of the beta-silicon nitride accounts for 0.2-2.5% of the spherical aluminum nitride, the mass of the high-purity silicon powder accounts for 2.0-5.0%, and the mass of the sintering aid accounts for 0.01-0.20%.

4. The method for preparing β-silicon nitride-coated spherical aluminum nitride according to claim 2, characterized in that: The outlet air temperature of spray drying is 80-100℃.

5. The method for preparing β-silicon nitride coated spherical aluminum nitride according to claim 2, characterized in that: The debinding process is carried out in an air atmosphere at 300-600℃.

6. The method for preparing β-silicon nitride coated spherical aluminum nitride according to claim 2, characterized in that: The calcination temperature is 1450-1750°C.

Citation Information

Patent Citations

  • Method for producing silicon oxide-coated aluminum nitride powder and silicon oxide-coated aluminum nitride powder

    JP2023088509A

  • Method for synthesizing silicon nitride powder by nitriding silicon powder under conditions of medium temperature and micro positive pressure

    CN102503434A

  • Preparation method of silicon nitride

    CN110240131A

  • Spherical Si and silicon nitride ceramic powder as well as preparation method and application thereof

    CN117003562A

  • Production of silicon nitride powder

    JP1997025107A